The attitudes of incest offenders - Hanson, Robert Karl (Criminal justice and behavior, 1994)
The attitudes of child molesters often are considered to contribute to their offenses, and the accurate identification of these cognitive distortions can be important to assessment and treatment. Through the administration of a newly created questionnaire, the attitudes of 50 male incest offenders were compared with those of 25 male batterers and 25 men not seeking treatment. Compared to the other groups, the incest offenders showed deviant attitudes in three domains: (a) endorsing attitudes supportive of male sexual privilege (sexual entitlement), (b) perceiving children to be sexually attractive and sexually motivated, and (c) minimizing the harm caused by sexual abuse of children. Implications of the findings for theories of father-daughter incest are discussed